Noncrystalline Binder Based Composite Propellant. (24th September 2013) - Abdullah, Mohamed; Gholamian, F.; Zarei, A. R.
Abstract : This study reports on propellants based on cross-linked HTPE binder plasticized with butyl nitroxyethylnitramine (BuNENA) as energetic material and HP 4000D as noncrystalline prepolymer. This binder was conducted with solid loading in the 85%. The results showed an improvement in processability, mechanical properties and burning rate. In addition, its propellant delivers (about 6 seconds) higher performance (specific impulse) than the best existing composite solid rocket propellant. Thermal analyses have performed by (DSC, TGA). The thermal curves have showed a low glass transition temperature (T g ) of propellant samples, and there was no sign of binder polymer crystallization at low temperatures (−50°C). Due to its high molecular weight and unsymmetrical or random molecule distributions, the polyether (HP 4000D) has been enhanced the mechanical properties of propellants binder polymer over a large range of temperatures [−50, 50°C]. The propellants described in this paper have presented high volumetric specific impulse (>500 s·gr·cc −1 ). These factors combined make BuNENA based composite propellant a potentially attractive alternative for a number of missions demanding composite solid propellants.